2019
DOI: 10.1002/adfm.201807872
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic–Salt Composite Electrolytes from Cold Sintering

Abstract: The development of solid electrolytes with the combination of high ionic conductivity, electrochemical stability, and resistance to Li dendrites continues to be a challenge. A promising approach is to create inorganic-organic composites, where multiple components provide the needed properties, but the high sintering temperature of materials such as ceramics precludes close integration or co-sintering. Here, new ceramic-salt composite electrolytes that are cold sintered at 130 °C are demonstrated. As a model sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 50 publications
0
58
0
Order By: Relevance
“…5 Al 0.5 Ge 1.5 (PO 4 ) 3 -(-CH 2 CF 2 -) x [-CF 2 CF(CF 3 )-] y , 16 Li 1. 5 Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP) or Li 1+x+y Al x Ti 2−x Si y P 3y O 12 (LATP) with bis(trifluoromethanesulfonyl)imide (LiTFSI) salts showing similar room temperature conductivity (10 −4 S·cm −1 ) as conventionally sintered ceramics, 17 Li-ion cathode LiFePO 4 -Polyvinylidene fluoride with enhanced electrochemical performances, 18 semiconductor V 2 O 5 -poly(3,4-ethylenedioxythiophene) polystyrene sulfonate composites with engineered mechanical, thermal, and electronic properties. 19 These studies highlight the new opportunities for high ceramic volume fraction (v/v >95%) ceramic-thermoplastic polymer composites enabled by cold sintering.…”
Section: Introductionmentioning
confidence: 99%
“…5 Al 0.5 Ge 1.5 (PO 4 ) 3 -(-CH 2 CF 2 -) x [-CF 2 CF(CF 3 )-] y , 16 Li 1. 5 Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP) or Li 1+x+y Al x Ti 2−x Si y P 3y O 12 (LATP) with bis(trifluoromethanesulfonyl)imide (LiTFSI) salts showing similar room temperature conductivity (10 −4 S·cm −1 ) as conventionally sintered ceramics, 17 Li-ion cathode LiFePO 4 -Polyvinylidene fluoride with enhanced electrochemical performances, 18 semiconductor V 2 O 5 -poly(3,4-ethylenedioxythiophene) polystyrene sulfonate composites with engineered mechanical, thermal, and electronic properties. 19 These studies highlight the new opportunities for high ceramic volume fraction (v/v >95%) ceramic-thermoplastic polymer composites enabled by cold sintering.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the use of an optimal SSE can significantly increase energy density and improve safety performance owing to its wide electrochemical window and non‐flammability. Several solid electrolytes based on polymer, [ 4 ] ceramic oxides, [ 5 ] ceramic sulfides, [ 6 ] and hybrid polymer‐ceramic [ 7 ] materials have been reported and applied in ASSLB studies. Among them, NASICON‐structured phosphate‐based electrolytes, Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP) [ 8,9 ] and Li 1.5 Al 0.5 Ti 1.5 (PO 4 ) 3 (LATP), [ 10 ] have attracted significant attention due to their high ionic conductivity (around 10 −4 S cm −1 ), high voltage stability (up to 5 V), and excellent moisture stability.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the low temperature, the key processing advantages of CSP are that it produces a near shape, that the prepared dense ceramic possesses the same diameter as the model, and that no reaction occurs between different ingredients. Randall et al reported the fabrication and electrochemical properties of ceramic-salt composite electrolytes from cold sintering (Lee et al, 2019). Reaney et al addressed cold sintered C0G mulitlayer ceramic capacitors with Ag internal electrodes (Wang et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%